An Embodied Approach to Understanding: Making Sense of the World Through Simulated Bodily Activity - Soylu, Firat (Frontiers in Psychology, 2016)
Even though understanding is a very widely used concept, both colloquially and in scholarly work, its definition is nebulous and it is not well-studied as a psychological construct, compared to other psychological constructs like learning and memory. It is hard to study understanding based on third-person behavioral data or neural data alone. Understanding refers to a first-person experience of making sense of an event or conceptual domain, and therefore requires incorporation of multiple levels of study, at the first-person (phenomenological), behavioral, and neural levels. Previously, psychological understanding was defined as a form of conscious knowing. Alternatively, biofunctional approach not only refers to conscious knowing but also extends to unconscious, implicit, automatic, and intuitive aspects of cognition. Here, to bridge these two approaches an embodied and evolutionary perspective is provided to situate biofunctional understanding in theories of embodiment, and to discuss how simulation theories of cognition, which regard simulation of sensorimotor and affective states as a central tenet of cognition, can bridge the gap between biofunctional and psychological understanding.